2021
DOI: 10.1039/d1sc04283a
|View full text |Cite
|
Sign up to set email alerts
|

Galbofloxacin: a xenometal-antibiotic with potent in vitro and in vivo efficacy against S. aureus

Abstract: Siderophore-antibiotic drug conjugates are considered potent tools to deliver and potentiate the antibacterial activity of antibiotics, but only few have seen preclinical and clinical success. Here, we introduce the gallium(III)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…58 The Ga(III) complex with maltolate 59 was reported to show anti-planktonic properties against S. aureus, while recent success of galbofloxacin, a ciprofloxacincontaining gallium compound, demonstrates success of a combinational approach to gallium-bearing drugs development against S. aureus. 60 In our studies, bacteriostatic properties against S. aureus were observed from all co-crystallization products. Beyond the silver co-crystals (CC-1/2) having good antibiofilm properties, the zinc co-crystal (CC-6) has excellent antibiofilm activity, even though its bacteriostatic activity is less effective.…”
Section: ■ Discussionmentioning
confidence: 55%
“…58 The Ga(III) complex with maltolate 59 was reported to show anti-planktonic properties against S. aureus, while recent success of galbofloxacin, a ciprofloxacincontaining gallium compound, demonstrates success of a combinational approach to gallium-bearing drugs development against S. aureus. 60 In our studies, bacteriostatic properties against S. aureus were observed from all co-crystallization products. Beyond the silver co-crystals (CC-1/2) having good antibiofilm properties, the zinc co-crystal (CC-6) has excellent antibiofilm activity, even though its bacteriostatic activity is less effective.…”
Section: ■ Discussionmentioning
confidence: 55%
“…In a recent study, Boros and her team designed a special version of a siderophore that binds to gallium instead of iron. 5 The bacteria are tricked into transporting the gallium…”
Section: Tricking Bacteriamentioning
confidence: 99%
“…26 More recently, we demonstrated that the xenometallomycin concept can yield compounds that exceed the potency of the parent antibiotic in vitro and in vivo with the second-generation compound Ga-D5 (Figure 1). 27 However, while synthetic siderophore antibiotic conjugates have been extensively explored, the structure− activity relationship remains difficult to predict. Furthermore, the exact mechanism of the antiproliferative activity of Ga(III) siderophore complexes is not well established and requires further study.…”
mentioning
confidence: 99%
“…These conjugates act as “Trojan Horses” and take advantage of the bacterial iron assimilation pathway to deliver antibiotics to the cytoplasm. Miller, Nolan, Bronstrupp, Duhme-Klair, and Wencewicz ,, have demonstrated that this strategy is not only efficacious but also provides insights into the frequently complex bacterial iron acquisition pathways. Our group focuses on xenometallomycins, which are Trojan horse conjugates that incorporate a nonendogenous metal ion for co-delivery and to enhance bactericidal activity. , We hypothesize that nonendogenous metal ions can exert additional, metal-based toxicity, to further enhance compound potency and attenuate bacterial resistance. We have previously successfully validated this approach with siderophore antibiotic conjugates Ga- D1 , Ga- D2, and Ga- D5 (Figure ), inspired by the structures of the natural product antibiotics salmycin and albomycin. Our constructs comprised three components: (1) the metal-bound siderophore, (2) a noncleavable linker, and (3) a fluoroquinolone-based antibiotic.…”
mentioning
confidence: 99%
See 1 more Smart Citation